Variations in Dream Recall Frequency and Dream Theme Diversity by Age and Sex - Nielsen, Tore (Frontiers in Neurology, 2012)
We assessed dream recall frequency and dream theme diversity with an internet questionnaire among a cohort of 28,888 male and female participants aged 10 to 79 years in a cross-sectional design. Dream recall frequency increased from adolescence (ages 10-19) to early adulthood (20-29) and then decreased again for the next 20 years. The nature of this decrease differed for males and females. For males, it began earlier (30-39), proceeded more gradually, and reached a nadir earlier (40-49) than it did for females. For females, it began later (40-49), dropped more abruptly, and reached nadir later (50-59). Marked sex differences were observed for age strata 10-19 through 40-49 and year-by-year analyses estimated the window for these differences to be more precisely from 14-44 yrs. Dream theme diversity decreased linearly with age for both sexes up to 50-59 and then dropped even more sharply for 60-79. There was a sex difference favouring males on this measure but only for ages 10-19. Findings replicate, in a single sample, those from several previous studies showing an increase in dream recall frequency from adolescence to early adulthood, a subsequent decrease in dream recall frequency—primarily in early and middle adulthood, and different patterns of age-related decrease in the two sexes. Age-related changes in sleep structure, such as decreasing %REM sleep, parallel the observed dream recall changes but are much smaller and more gradual in nature. Changes in the phase and amplitude of circadian rhythms of REM propensity and generational differences in life experiences may also account for some part of the findings. However, that decreases in dream theme diversity parallel known age-related decreases in episodic and autobiographical memory may signify that the diversity measure indexes an aspect of autobiographical memory that is specific to dream recall.